ANALISIS KEMAMPUAN BERPIKIR KRITIS MAHASISWA DALAM MEMAHAMI KONSEP HUKUM NEWTON - Hidayah, Nurul (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This research is motivated by the urgency of mastering critical thinking skills in Elementary School Teacher Education (PGSD) students as an essential competency in transforming abstract science concepts, especially Newton's Laws, into meaningful learning for elementary school students. The weakness in understanding basic physics concepts at the teacher candidate level is feared to have a systemic impact on the quality of science education at the elementary level. This quantitative descriptive research aims to analyze the profile of critical thinking skills of 16 3rd semester PGSD students in solving Newton's Law problems using an open-ended test instrument referring to the indicators of Erceg. The research findings indicate that the level of critical thinking of students is still relatively low, with quantitative data revealing that in question number 1.1, only 87.5% of students answered correctly; in question 1.2, the percentage of correct answers decreased drastically to 6.25% with 87.5% answering incorrectly; and in question number 2 which requires in-depth analysis, all students (100%) gave incorrect answers. The main conclusion of this study indicates that students tend to solve problems based only on logical intuition without a strong foundation in physics concepts, so that more effective learning methodology interventions are needed to improve critical thinking capacity and reduce misconceptions in basic mechanics material. ABSTRAK Penelitian ini dilatarbelakangi oleh urgensi penguasaan keterampilan berpikir kritis pada mahasiswa Pendidikan Guru Sekolah Dasar (PGSD) sebagai kompetensi esensial dalam mentransformasikan konsep sains abstrak, khususnya Hukum Newton, menjadi pembelajaran yang bermakna bagi siswa sekolah dasar. Kelemahan pemahaman konsep fisika dasar di tingkat calon guru dikhawatirkan berdampak sistemik pada kualitas pendidikan sains di jenjang dasar. Penelitian deskriptif kuantitatif ini bertujuan untuk menganalisis profil kemampuan berpikir kritis 16 mahasiswa PGSD semester 3 dalam menyelesaikan persoalan Hukum Newton menggunakan instrumen tes open-ended yang mengacu pada indikator Erceg. Temuan penelitian menunjukkan bahwa tingkat berpikir kritis mahasiswa masih tergolong rendah, dengan data kuantitatif mengungkapkan bahwa pada soal nomor 1.1, hanya 87,5% mahasiswa menjawab benar; pada soal 1.2, persentase jawaban benar menurun drastis menjadi 6,25% dengan 87,5% menjawab salah; dan pada soal nomor 2 yang menuntut analisis mendalam, seluruh mahasiswa (100%) memberikan jawaban salah. Simpulan utama studi ini mengindikasikan bahwa mahasiswa cenderung menyelesaikan masalah hanya berdasarkan intuisi logika tanpa landasan konsep fisika yang kuat, sehingga diperlukan intervensi metodologi pembelajaran yang lebih efektif untuk meningkatkan kapasitas berpikir kritis dan mereduksi miskonsepsi pada materi mekanika dasar.